Of pedagogy and potentiality: Embodied learning and collaborative storytelling through pop-up exhibits. - Settoducato, Elizabeth. (Tufts University. Tisch Library., 2018)
Pop-up exhibits are a promising opportunity for inclusive and educational library instruction. As academic librarians’ teaching evolves in response to and in anticipation of our communities’ needs, we must think broadly and intentionally about the tools and strategies we use to facilitate inclusive, collaborative instruction experiences.; Keywords: pop-up exhibits, instruction, outreach, collaboration, pedagogy.